Impaired neural response to speech edges in dyslexia. (February 2021) - Lizarazu, Mikel; Lallier, Marie; Bourguignon, Mathieu; Carreiras, Manuel; Molinaro, Nicola
Abstract: Speech comprehension has been proposed to critically rely on oscillatory cortical tracking, that is, phase alignment of neural oscillations to the slow temporal modulations (envelope) of speech. Speech-brain entrainment is readjusted over time as transient events (edges) in speech lead to speech-brain phase realignment. Auditory behavioral research suggests that phonological deficits in dyslexia are linked to difficulty in discriminating speech edges. Importantly, research to date has not specifically examined neural responses to speech edges in dyslexia. In the present study, we used MEG to record brain activity from normal and dyslexic readers while they listened to speech. We computed phase locking values (PLVs) to evaluate phase entrainment between neural oscillations and the speech envelope time-locked to edge onsets. In both groups, we observed that edge onsets induced phase resets in the auditory oscillations tracking speech, thereby enhancing their entrainment to speech. Importantly, dyslexic readers showed weaker PLVs compared to normal readers in left auditory regions from ~.15 sec to ~.65 sec after edge onset. Our results indicate that the neural mechanism that adapts cortical entrainment to the speech envelope is impaired in dyslexia. These findings here are consistent with the temporal sampling theory of developmental dyslexia.